Feasibility Evaluation of Milling Designs Using Multi-Agent Systems. (May 2022) - Plappert, S.; Becker, C.; Gembarski, P. C.; Lachmayer, R.
Abstract: During product development, many decisions have to be made that affect the entire product life cycle and often lead to errors that cause additional effort. To proactively support the engineer in evaluating his design in a CAD program, in this paper an approach to evaluate milling designs using a multi-agent system (MAS) is presented. The CommonKADS method is used and the MAS is validated against an application example of a gearbox housing that has been checked for design guidelines, standards, and tool or machine portfolios.